Cognitive Assessment of PJOK Subjects Using Paper Mode In The Quizizz Application - Robby Dzulfaqor Noor; Yerdi Pratma; Ares Lumban Gaol; Dewii Susilawat (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
The process of assessing student learning is an important part of efforts to collect information about learning outcomes.  The use of technology  (computers)  makes this process more efficient. Paper Mode Quizizz is a platform that attracts students' interest and increases student focus. The purpose of this research is to be able to arouse interest and increase students'  concentration.  This study used a qualitative descriptive method to describe the interest and concentration conditions of the sixth-grade students at  SDN Bangkir. This study used various tools to collect data, including (1) observation sheets, (2) student questionnaires; and (3) interview guidelines to support the results of the student response questionnaire. The results showed that the Paper Mode Quizizz application could increase student interest by  87.6%  and student concentration by  87.2%  by working on assessment questions to achieve optimal results.